2017
DOI: 10.2135/cropsci2016.08.0713
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Row Spacing and P and N Applications on Seed Yield Components and Seed Yield of Siberian Wildrye (Elymus sibiricusL.)

Abstract: Siberian wildrye (Elymus sibiricus L.) is a globally important cool‐season forage grass for semiarid regions. However, its seed yield is often low or inconsistent. As previous studies examined the effects of row spacing and P and N levels on seed production of Siberian wildrye separately, this study was focused on the combined effects of four row spacings (30, 45, 60, 75 cm), four P application levels (0, 60, 90, 120 kg P ha−1), and four N application levels (0, 30, 60, 90 kg N ha−1). Treatments were establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Path coefficients were compared between submodels using the function plspm.groups of the plspm package. Path analysis has previously been used to evaluate the effects of management on yield formation in perennial grasses (e.g., Seker & Serin, 2004; Wang et al., 2017) and to evaluate the physiological effects of selection for grain yield in intermediate wheatgrass (Cattani & Asselin, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Path coefficients were compared between submodels using the function plspm.groups of the plspm package. Path analysis has previously been used to evaluate the effects of management on yield formation in perennial grasses (e.g., Seker & Serin, 2004; Wang et al., 2017) and to evaluate the physiological effects of selection for grain yield in intermediate wheatgrass (Cattani & Asselin, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Seed samples were taken from the center of each plot to avoid border effects. Because of serious seed shattering reported in this species [1], seeds were harvested when the seed moisture content was approximately 45% [44]. Seeds of each plant were air-dried, carefully threshed, cleaned, weighed and stored in paper bags at 20 • C and 15% relative humidity before subjected to seed yield evaluation and other seed measurements.…”
Section: Study Areamentioning
confidence: 99%
“…To the best of our knowledge, no studies have reported the microbial succession of whole-plant corn silages ensiled with LAB prepared from whole-plant corn silages and other silages. Elymus sibiricus is a tall-growing and perennial bunchgrass widely distributed in Europe, Asia, and North America ( Klebesadel, 1969 ), and used as forage because of high yield potential and good quality ( Wang et al, 2017 ). Moreover, E. sibiricus has become a grass for artificial grassland and been ensiled for ruminants in China ( Sun et al, 2009 ; Li et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%